Neuroblastoma neck in a 7-year-old girl: a very rare presentation (Journal of Paediatric Surgeons of Bangladesh, 2015)
Neuroblastoma in neck is a very rare presentation. The age range of neuroblastoma is broad, but only 10% of cases are reported in people older than 5years of age, and is most commonly diagnosed in children before age of 5years (with highest incidence in the first year of life), being slightly more common in boys. The girl child reported in our case, being mere 7 years old, presented with bilateral hard neck swellings, was not clinically suspected of this rare presentation, until Immunohistochemistry confirmed the diagnosis. This report underscores the need for prompt evaluation of patients (especially children) with common symptoms and uncommon presentation of the disease entity.J. Paediatr. Surg. Bangladesh 3(2): 88-91, 2012 (July)